Analysis of Audit Delay Determinants: An Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Ali, M. Khairun Najmi; Yudi; Gowon, Muhammad (Indonesian Journal of Economic & Management Sciences, 2024)
This research investigates the impact of profitability, capital structure, and liquidity on audit delay. Employing a quantitative approach, the study utilizes secondary data sourced from the Indonesia Stock Exchange (IDX) for companies in the property and real estate sector from 2020 to 2023. A purposive sampling technique was applied, resulting in a sample of 91 companies. Descriptive statistics and multiple linear regression were used to analyze the data with SPSS software (version 26) at a 5% significance level. The findings reveal that profitability and capital structure both significantly influence audit delay, while liquidity does not have a significant impact. Additionally, the combined effects of profitability, capital structure, and liquidity on audit delay were found to be significant.